The effect of word of mouth and brand image on consumer purchasing decisions at PS Cosmetic Store in Sidenreng Rappang Regency - Mariana Mariana; Andi Riska Andreani Syafaruddin; Rahman Yakub; Bahtiar Herman (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates the influence of word of mouth (WOM) and brand image on purchase decisions at PS Kosmetik Store in Sidenreng Rappang Regency. A quantitative explanatory approach was employed using survey data collected from 351 consumers selected through purposive sampling based on the Slovin formula. Data were analyzed using multiple linear regression with SPSS 26 to examine both the individual and combined effects of the independent variables. The findings indicate that WOM and brand image each have a positive and significant effect on purchase decisions. Simultaneously, both variables significantly explain purchase decisions, accounting for 53.0% of the observed variance (R² = 0.530). The results suggest that positive customer recommendations and a strong brand image play complementary roles in shaping consumer purchasing behavior. This study highlights the importance of strengthening customer communication strategies and maintaining a favorable brand image to enhance consumer trust, encourage purchase decisions, and improve retail competitiveness. Keywords: Word of Mouth (WOM); Brand Image; Purchase Decision